Democratic discourses : the radical abolition movement and antebellum American literature - Bennett, Michael, 1962- (Rutgers University Press, 2005)
In this path-breaking study, Michael Bennett departs from tradition to argue that the democratic ideal of equality and the actual ways in which it has been practiced are grounded less in the fledgling government documents written by a handful of white men than in the actions and writings of the radical abolitionists of the nineteenth century. Bringing together key texts of both African American and European American authors, Democratic Discourses shows the important ways that abolitionist writing shaped a powerful counterculture within a slave-holding society. Bennett offers fresh new analysis through unusual pairings of authors, including Frederick Douglass with Henry David Thoreau, Frances Ellen Watkins Harper with Walt Whitman, and Margaret Fuller with Sojourner Truth. These rereadings avoid the tendency to view antebellum writing as a product primarily of either European American or African American influences and, instead, illustrate the interconnections of white and black literature in the creation and practice of democracy. Drawing on discourses about race, the body, gender, economics, and aesthetics, this unique study encourages readers to reconsider the reality and roots of freedoms experienced in the United States today.